Risk of Climate-Related Impacts on Global Rangelands - A Review and Modelling Study - Godde, Cécile M.; Boone, R.B.; Ash, A.; Waha, K.; Sloat, L.; Thornton, Philip K.; Mason-D'Croz, Daniel; Mayberry, D.; Herrero, Mario (International Livestock Research Institute, 2021)
Climate change threatens the ability of global rangelands to provide food, support livelihoods and deliver important ecosystems services. The extent and magnitude of potential impacts are however poorly understood. In this study, we review the risk of climate impacts along the rangeland systems food supply chain. We also present results from biophysical modelling simulations and spatial data analyses to identify where and to what extent rangelands may be at climatic risk. Although a quantification of the net impacts of climate change on rangeland production systems is beyond the reach of our current understanding, there is strong evidence that there will be impacts throughout the supply chain, from feed and animal production to processing, storage, transport, retailing and human consumption. Regarding grazing biomass production, this study finds that mean herbaceous biomass is projected to decrease across global rangelands between 2000 and 2050 under RCP 8.5 (-4.7%), while inter- (year-to-year) and intra- (month-to-month) annual variabilities are projected to increase (+21.3% and +8.2%, respectively). These averaged global estimates mask large spatial heterogeneities, with 74% of global rangeland area projected to experience a decline in mean biomass, 64% an increase in inter-annual variability and 54% an increase in intra-annual variability. The potentially most damaging vegetation trends for livestock production (i.e., simultaneous decreases in mean biomass and increases in inter-annual variability) are projected to occur in rangeland communities that are currently the most vulnerable (here, with the lowest livestock productivities and economic development levels and with the highest projected increases in human population densities). Large uncertainties remain as to climate futures and the exposure and responses of the interlinked human and natural systems to climatic changes over time. Consequently, adaptation choices will need to build on robust methods of designing, implementing and evaluating detailed development pathways, and account for a wide range of possible futures.